2001
DOI: 10.1063/1.1421416
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electroluminescence intensity of green and blue InGaN single-quantum-well light-emitting diodes

Abstract: Temperature dependence of electroluminescence (EL) spectral intensity of the super-bright green and blue InGaN single-quantum-well (SQW) light-emitting diodes has been studied over a wide temperature range (T=15–300 K) under a weak injection current of 0.1 mA. It is found that when T is slightly decreased to 140 K, the EL intensity efficiently increases, as usually seen due to the improved quantum efficiency. However, with further decrease of T down to 15 K, it drastically decreases due to reduced carrier capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
43
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 10 publications
10
43
1
Order By: Relevance
“…The weaker but higher-energy peak was then attributed to the corresponding transition predicted for a random alloy of InGaN matrix. Hori et al 5,6 studied the temperature-dependent EL spectra in efficient blue and green LEDs produced also by Nichia, showing general features very similar to our observation. They had attributed the higher-energy peak possibly to GaN, although a large redshift was noticed compared with the band gap of GaN.…”
Section: Experiments and Discussionsupporting
confidence: 65%
“…The weaker but higher-energy peak was then attributed to the corresponding transition predicted for a random alloy of InGaN matrix. Hori et al 5,6 studied the temperature-dependent EL spectra in efficient blue and green LEDs produced also by Nichia, showing general features very similar to our observation. They had attributed the higher-energy peak possibly to GaN, although a large redshift was noticed compared with the band gap of GaN.…”
Section: Experiments and Discussionsupporting
confidence: 65%
“…Previously quantum confinement effects in the InGaN quantum well and efficient carrier capturing by localized radiative recombination centers in quantum-dot-like states [3][4][5][6] have been claimed to be important for the high emission efficiency. Our previous studies of the temperature-dependent electroluminescence (EL) intensity in single-QW (SQW) diodes [8] show that efficient capture processes of injected carriers by localized tail states play an important role between 180 and 300 K. However, for temperatures below 100 K, an anomalous quenching of the EL intensity is observed, which we attribute to reduced carrier capture rates.…”
Section: Introductionmentioning
confidence: 81%
“…24 Recently, an anomalous temperature-dependence of electroluminescence intensity in GaN-based LEDs was reported. [27][28][29][30] It was found that when temperature is decreased to around 200 K, the EL intensity rises, as expected from the improved quantum efficiency. However with a further decrease in temperature, the EL intensity falls dramatically.…”
Section: Discussionmentioning
confidence: 73%
“…However with a further decrease in temperature, the EL intensity falls dramatically. That phenomenon was explained by reduced carrier capture by QWs at low temperature, [27][28][29] or by the low ionization rate of magnesium (Mg) in p-GaN at low temperature. 30 In our simulation, Fig.…”
Section: Discussionmentioning
confidence: 99%